2009
DOI: 10.1590/s0102-86502009000200009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the bactericidal effect of ozone pneumoperitoneum

Abstract: Purpose:To assess the bactericidal action of ozone pneumoperitonium, and to compare the results with CO2. Methods: It was used 36 Wistar rats. The animals, under anesthesia, were inoculated with 2ml of E. coli ATCC at a concentration of 10 10 UFC, and 1ml of BaSO4, into the peritoneal cavity. They were divided into three groups: Group 1, CO2 pneumoperitoneum was performed for 15 minutes; Group 2, ozone pneumoperitoneum was performed for 5 minutes at a concentration of 42µg/ml, and Group 3, ozone pneumoperitone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
(13 reference statements)
0
25
0
1
Order By: Relevance
“…The lungs are the most affected organ, and pulmonary surfactant may be a target in ozone-induced lung toxicity (20). Moreover, toxic effects of ozone caused by excessive doses of inhaled ozone in the airways, as well as toxicity to the endocrine, reproductive, and central nervous systems, have been described (21,22). Although it has been demonstrated that an intrarectal or ip ozone/oxygen mixture reduced ROS by stimulation and/or preservation of the endogenous antioxidant systems in experimental models of liver and renal ischemia-reperfusion and radiation-induced organ injury, respectively (7,9,17,23,24), little is known about its side effects that are specifically related to free radical formation and irritation of the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…The lungs are the most affected organ, and pulmonary surfactant may be a target in ozone-induced lung toxicity (20). Moreover, toxic effects of ozone caused by excessive doses of inhaled ozone in the airways, as well as toxicity to the endocrine, reproductive, and central nervous systems, have been described (21,22). Although it has been demonstrated that an intrarectal or ip ozone/oxygen mixture reduced ROS by stimulation and/or preservation of the endogenous antioxidant systems in experimental models of liver and renal ischemia-reperfusion and radiation-induced organ injury, respectively (7,9,17,23,24), little is known about its side effects that are specifically related to free radical formation and irritation of the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…The bactericidal effect of O 3 is based on a direct attack on microorganisms by oxidation of biological materials. In fact, O 3 antibacterial activity can be more effective than iodine and chlorine 6,7. Data reported in the literature have shown that bacteria, spores, and viruses are inactivated by ozone after only few minutes of exposure8,9.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic effects of O 3 , caused by excessive doses of inhaled ozone in the airways, as well as toxicity to the endocrine, reproductive, and central nervous systems have been described7,12. Nevertheless, little is known about the intraperitoneal ( i.p .)…”
Section: Introductionmentioning
confidence: 99%
“…Stwierdzono, że ozon wykazywał większe działania bakteriobójcze niż CO 2 , ale tylko u zwierząt poddanych eutanazji bezpośrednio po aplikacji gazów. W próbkach pobranych po 24 h nie wykazano różnic w działaniu bójczym pomiędzy CO 2 a ozonem (37).…”
Section: Kliniczne Zastosowanie Ozonoterapiiunclassified